2016
DOI: 10.1007/s00299-016-1952-8
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine protects hulless barley from damage due to UV-B stress via H2S- and H2O2-mediated signaling pathways

Abstract: In hulless barley, H 2 S mediated increases in H 2 O 2 induced by putrescine, and their interaction enhanced tolerance to UV-B by maintaining redox homeostasis and promoting the accumulation of UV-absorbing compounds. This study investigated the possible relationship between putrescence (Put), hydrogen sulfide (H2S) and hydrogen peroxide (H2O2) as well as the underlying mechanism of their interaction in reducing UV-B induced damage. UV-B radiation increased electrolyte leakage (EL) and the levels of malondiald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 107 publications
1
18
0
3
Order By: Relevance
“…H 2 S began to decline with time, but it is overall significantly higher than that of the control (approximately 125 nmol g -1 FW) at 48 h of exposure. A similar trend was observed for LCD activity, which was corroborated by the application of DL -propargylglycine (PAG, an inhibitor of LCD) that resulted in complete inhibition of the H 2 S production and the accumulation of UV-absorbing compounds induced by UV-B radiation (Li et al, 2016). …”
Section: H2s Signaling Triggered By Abiotic Stresssupporting
confidence: 58%
See 1 more Smart Citation
“…H 2 S began to decline with time, but it is overall significantly higher than that of the control (approximately 125 nmol g -1 FW) at 48 h of exposure. A similar trend was observed for LCD activity, which was corroborated by the application of DL -propargylglycine (PAG, an inhibitor of LCD) that resulted in complete inhibition of the H 2 S production and the accumulation of UV-absorbing compounds induced by UV-B radiation (Li et al, 2016). …”
Section: H2s Signaling Triggered By Abiotic Stresssupporting
confidence: 58%
“…Recently, Li et al (2016) found that UV-B radiation could induce H 2 S production in leaves of barley seedlings, reaching a peak of approximately 230 nmol g - 1 FW after 12 h of exposure, which in turn promoted the accumulation of UV-absorbing compounds flavonoids and anthocyanins. H 2 S began to decline with time, but it is overall significantly higher than that of the control (approximately 125 nmol g -1 FW) at 48 h of exposure.…”
Section: H2s Signaling Triggered By Abiotic Stressmentioning
confidence: 99%
“…However, in the literature, we were able to find only indirect indications of the role of NADPH oxidase in ROS generation during the treatment of barley leaves with sodium hydrosulfide [12].…”
mentioning
confidence: 70%
“…As was noted, in only one work, using inhibitor of NADPH oxidase diphenyleniodonium, the possible participation of this enzyme as an ROS generator was shown when inducing the resistance of barley plants to the action of UV-B [12] by the exogenous hydrogen sulfide. In our work using the inhibitory method, the causal relationship between hydrogen sulfidestimulated and NADPH oxidase dependent superoxide anion radical generation, induction of antioxidant enzymes, and development of heat resistance of wheat coleoptiles was first demonstrated.…”
Section: Fig 3 Content Of Hydrogen Peroxide In Wheat Coleoptiles Unmentioning
confidence: 96%
See 1 more Smart Citation